Endovascular Therapy for Chronic Cerebrospinal Venous Insufficiency in Multiple Sclerosis - Lazzaro, Marc A.; Zaidat, Osama O.; Mueller-Kronast, Nils; Taqi, Muhammad A.; Woo, Douglas (Frontiers in Neurology, 2011)
Recent reports have emerged suggesting that multiple sclerosis (MS) may be due to abnormal venous outflow from the central nervous system, termed Chronic Cerebrospinal Venous Insufficiency (CCSVI). These reports have generated strong interest and controversy over the prospect of a treatable cause of this chronic debilitating disease. This review aims to describe the proposed association between CCSVI and MS, summarize the current data, and discuss the role of endovascular therapy and the need for rigorous randomized clinical trials to evaluate this association and treatment.